Forecasting of water intake and supply in water plant in Johor - Foo, Fong Ying; Nor, Maria Elena; Azli, Nor Amiratun Najwa (2021)
The safety and availability of water are important for public health, domestic use, food, and drink production process. Since water is essential in daily life, the demand for water intake and water supply are increasing. Moreover, it must be ensured that the water intake is sufficient to supply water towards the consumers. This is vital to avoid water scarcity in society. Thus, the main objective of this research is to forecast the water intake and water supply by adopting exponential smoothing and Box-Jenkins methods. Then, the forecast performance is evaluated by using mean error (ME), mean absolute scaled error (MASE) and mean absolute percentage error (MAPE). Further, the best model is used to forecast water intake and water supply for the next seven days. The daily data for three years of water intake and water supply in one of the water plants in Johor was collected. The forecast capabilities of the two different methods were compared. Both methods are fitted well but, in overall, the triple exponential smoothing method is outperformed compared to the Box-Jenkins method. This is due to the exponential smoothing method to produce less MAPE and ME values. Both datasets shared the same model which imply the water treatment system used is stable and in good condition. Besides, the water intake and water supply by using triple exponential smoothing method is predicted to be decreased in the following seven days.